Diseño institucional - organizacional y de procesos académicos de la carrera de gerencia y liderazgo de la Universidad Politécnica Salesiana - Aguilar Angueta, Jefferson Danny (2008)
First, we proceeded to identify the key internal and external factors that one way or another has affected education in the country and therefore the university in general; in this context, in chapter two, the analysis of the macro-environment and micro-environment of some variables that have directly affected the normal development of the School of Management and Leadership is performed, a sketch of the Salesian Polytechnic University is also performed analyzing its Organizational Structure.